Poligami: Antara Teks dan Konteks Sosial - Mukri, Moh. (Universitas Islam Negeri Raden Intan Lampung, 2017)
This article discusses the proposition of Syara’ concerning polygamy. The aim is to find out the relationship between literal meaning of the text and the socio-historical context underlying the issuance of the provosion. This study utilizes historical, textual approach to obtain a vivid, comprehensive perspective of the literal and contextual meaning. As it is already known, the proposition of polygamy is Surah an-Nisa’: [4]: 3 plus a number of hadiths relating the issue. According to history, the reasons underlying the revelation of Surah an-Nisa’: [4]: 3, actually, was to reprimand companions who wanted to marry orphans in their guardianship but unwilling to give dowry as much as when they married other women. Thus, the verse was not solely about polygamy or limitation of the number of wives, but it also contained a criticism against contemporary tradition which tended to be arbitrary in releasing lust. Furthermore, polygamy itself is not recommended nor even impulsive in Islam. As the above-mentioned shura implies, Islam prefers monogamy than polygamy, as it imposes difficult condition for those who want to do polygamy